Spatial and temporal distribution characteristics and influencing factors of cultural heritage: A case of the Grand Canal (East Zhejiang section)-maritime silk road - Jie Li; Xinlian Yang; Yuhe Gao; Chao Gao (PLoS ONE, 2025)
The Grand Canal and the Maritime Silk Road in China are globally significant cultural routes, which have contributed a wealth of cultural heritage through their historical development. The study on the cultural heritage of the Grand Canal (East Zhejiang section)-Maritime Silk Road is of great significance for constructing the Grand Canal Cultural Belt and advancing the Belt and Road Initiative. Focusing on the Ningbo area, this study analyzes the spatial and temporal distribution of 1,755 cultural heritage sites over five historical periods and explores the influencing factors through spatial and statistical analysis. The results show that: (1) Ancient buildings, along with modern important historical sites and representative buildings, are the most numerous. The total number of cultural heritages shows an upward trend before the modern period, peaking in the Ming to Qing period. (2) The cultural heritage exhibits an overall aggregated spatial distribution, with varying patterns across different types. The Three-River Estuary is the high-density core area, with the number and density of cultural heritage decreasing as its distance increases. (3) Distribution characteristics of cultural heritage vary across different periods. More recent cultural heritage is increasingly concentrated around the Three-River Estuary. Over time, the center of gravity of cultural heritage has shifted sequentially to the south, southeast, west, and north. (4) The cultural heritage tends to be distributed in plain with low altitude and small slope, and shows strong hydrophilicity.